2019
DOI: 10.1021/acs.jpclett.9b01949
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Modification of VTe2 and Its Charge Density Wave

Abstract: Interlayer interactions in layered transition metal dichalcogenides are known to be important for describing their electronic properties. Here, we demonstrate that the absence of interlayer coupling in monolayer VTe2 also causes their structural modification from a distorted 1T′ structure in bulk and multilayer samples to a hexagonal 1T structure in the monolayer. X-ray photoemission spectroscopy indicates that this structural transition is associated with electron transfer from the vanadium d bands to the tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 39 publications
5
54
0
Order By: Relevance
“…The formation of such ordered intercalation compounds may also explain some controversial results regarding possible distorted lattices for ultrathin TMDC-films formed by direct MBE growth at elevated growth temperatures. 22,23,26,44 Transformation of layered chalcogenides into a different compositional phase by chalcogen-desorption induced by annealing or electron beam irradiation has been reported previously for other systems. 45,46,47,48,49 Thus, the transformations observed here fall into the same general category of phase engineering of layered materials and demonstrates that post-growth processing of ultrathin layered materials is a common approach for synthesizing new van der Waals materials.…”
Section: Discussionsupporting
confidence: 53%
“…The formation of such ordered intercalation compounds may also explain some controversial results regarding possible distorted lattices for ultrathin TMDC-films formed by direct MBE growth at elevated growth temperatures. 22,23,26,44 Transformation of layered chalcogenides into a different compositional phase by chalcogen-desorption induced by annealing or electron beam irradiation has been reported previously for other systems. 45,46,47,48,49 Thus, the transformations observed here fall into the same general category of phase engineering of layered materials and demonstrates that post-growth processing of ultrathin layered materials is a common approach for synthesizing new van der Waals materials.…”
Section: Discussionsupporting
confidence: 53%
“…Room-temperature ferromagnetism has been observed in VTe2 nanoplates 2 . However, FM order was absent in monolayer VTe2 according to 3 / 18 recent experimental studies 36,37 . The interplay between the long-range charge and spin orders in monolayer VTe2 is yet unknown.Here we investigate the different CDW phases in monolayer VTe2 by STM/STS and DFT calculations.…”
mentioning
confidence: 87%
“…Since the late 1950s, both CDW and magnetic orderings have been separately reported in VTe 2 of various thicknesses;15–19,21 in the former studies, however, the powder and thin film‐based VTe 2 materials showed conflicting features regarding their lattice structure at room temperature 19,20,22. Recent studies of thin VTe 2 films show that the interlayer interaction plays a role for the structural changes 18,23,24. However, no study on possible polymorphic quantum states from high‐quality VTe 2 single crystals has been performed.…”
Section: Electrical Properties Of the Types 1 And 2 Cdw Phases In Vtementioning
confidence: 99%